A rare case of inflammatory myofibroblastic tumor of the mandible mimicking a malignant tumor - Mohammed Ghazi AlKindi (Elsevier, 2017)
Inflammatory myofibroblastic tumor (IMT) of the head and neck is a rare benign proliferative lesion of unknown etiology that mimics malignant lesions clinically and radiographically. I report the case of a 27-year-old woman who presented with a mass in her left mandible associated with restricted mouth opening that had developed over the preceding 7 months. The mass was resected completely with 5 mm margin under general anesthesia. The mass was extending to the floor of the mouth and impinging on the masseter and temporalis muscles. Given its characteristics of being localized and aggressive, complete surgical resection is the best treatment modality for IMT. Keywords: Mandible, Inflammatory myofibroblastic tumor, Inflammatory pseudotumor, Oral cavity